Buildings that changed history - Wilkinson, Philip, 1955- (DK Publishing, a division of Penguin Random House LLC, 2025)
Buildings That Changed History gives you an overview of the history of architecture from the ancient world to the present day. It takes you on guided tours of more than 50 masterpieces of every architectural style, from the Great Pyramid of Giza to Chartres Cathedral, Sydney Opera House, and the Guggenheim Museum in Bilbao. Each building is analyzed visually. CGI cutaway artwork peels away roofs and walls to reveal the bones of the building, and close-up photographs home in on details of style.